Disrupted intrinsic networks link amyloid-β pathology and impaired cognition in prodromal Alzheimer's disease - Koch, Kathrin; Myers, Nicholas E.; Goettler, Jens; Pasquini, Lorenzo; Grimmer, Timo; Foerster, Stefan; Manoliu, Andrei; Neitzel, Julia; Kurz, Alexander; Foerstl, Hans; Riedl, Valentin; Wohlschlaeger, Afra M.; et al. (Cerebral Cortex, 2015)
Amyloid-β pathology (Aβ) and impaired cognition characterize Alzheimer's disease (AD); however, neural mechanisms that link Aβ-pathology with impaired cognition are incompletely understood. Large-scale intrinsic connectivity networks (ICNs) are potential candidates for this link: Aβ-pathology affects specific networks in early AD, these networks show disrupted connectivity, and they process specific cognitive functions impaired in AD, like memory or attention. We hypothesized that, in AD, regional changes of ICNs, which persist across rest-and cognitive task-states, might link Aβ-pathology with impaired cognition via impaired intrinsic connectivity. Pittsburgh compound B (PiB)-positron emission tomography reflecting in vivo Aβ-pathology, resting-state fMRI, task-fMRI, and cognitive testing were used in patients with prodromal AD and healthy controls. In patients, default mode network's (DMN) functional connectivity (FC) was reduced in the medial parietal cortex during rest relative to healthy controls, relatively increased in the same region during an attention-demanding task, and associated with patients' cognitive impairment. Local PiB-uptake correlated negatively with DMN connectivity. Importantly, corresponding results were found for the right lateral parietal region of an attentional network. Finally, structural equation modeling confirmed a direct influence of DMN resting-state FC on the association between Aβ-pathology and cognitive impairment. Data provide evidence that disrupted intrinsic network connectivity links Aβ-pathology with cognitive impairment in early AD.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Amyloid plaques; Impaired cognition; Intrinsic connectivity networks; PiB-PET; Prodromal Alzheimer's disease; resting-state fMRI; Task-fMRI